Propolis effects in periodontal disease seem to affect coronavirus disease: a meta-analysis - Silvia Helena de Carvalho SALES-PERES; Lucas José de AZEVEDO-SILVA; Ana Virginia Santana Sampaio CASTILHO; Marcelo Salmazo CASTRO; André de Carvalho SALES-PERES; Maria Aparecida de Andrade Moreira MACHADO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This meta-analysis aimed to investigate the effects of propolis on the severity of coronavirus disease symptoms by reducing periodontal disease. PubMed, EMBASE, SciELO, Web of Science, and SCOPUS databases were systematically searched. Studies have been conducted analyzing propolis's effects on COVID-19 and periodontitis. The study was conducted according to the PRISMA statement and registered in PROSPERO. Risk of Bias (RoB) assessment and meta-analysis of clinical studies were performed (Review Manager 5, Cochrane). The certainty of the evidence was assessed using GradePro (GDT). Studies have shown propolis flavonoids inhibit viral replication in several DNA and RNA viruses, including coronaviruses. Propolis components have an aminopeptidase inhibitor activity that can inhibit the main proteases of SARS viruses and seem to inhibit protein spikes, which are sites of most mutations in SARS-CoV strains. The meta-analysis showed favorable results with the use of propolis on probing depth (95%CI: 0.92; p < 0.001), clinical attachment level (95%CI: 1.48; p < 0.001), gingival index (95%CI: 0.14; p = 0.03), plaque index (95%CI: 0.11; p = 0.23), and blending on probing (95%CI: 0.39; p < 0.001). The antibacterial activity of propolis could be mediated through its direct action on microorganisms or the stimulation of the immune system, activating natural defenses. Thus, propolis inhibits the replication of SARS-CoV-2 as well as its bacterial activity. Treatment with propolis improves general health and facilitates the activation of the immune system against coronavirus.